2022
DOI: 10.47750/pnr.2022.13.s03.286
|View full text |Cite
|
Sign up to set email alerts
|

Automated Systems as a Factor Affecting on Flowers Plant Harvesting

Abstract: In the last decade, the adoption of fully automated systems in agricultural operations has become an urgent need due to high labor costs and low efficiency. The harvesting process is one of those agricultural activities that require a lot of work in addition to high costs. The study investigates different fully automated harvesting systems for one of the most important crops, medicinal and aromatic plants, especially flowers which are involved in many industries and characterized by high economic importance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In the literature [6][7], the formation of microporous silica gels corresponds to H2O/TEOS ratio values higher than 10. Therefore, experiments to determine the optimal ratio of H2O/TEOS were conducted in the range of H2O/TEOS ratio from 10 to 35.…”
Section: µM µMmentioning
confidence: 96%
“…In the literature [6][7], the formation of microporous silica gels corresponds to H2O/TEOS ratio values higher than 10. Therefore, experiments to determine the optimal ratio of H2O/TEOS were conducted in the range of H2O/TEOS ratio from 10 to 35.…”
Section: µM µMmentioning
confidence: 96%
“…The advantages and disadvantages of the sensor based on TiO2 are revealed. It has been shown that for further development in this area of science and technology, it is required to expand the range of materials through the use of binary and multicomponent titanium-containing mixtures of metal oxides with sensor properties [4]. Thanks to intensive experimental and theoretical research, significant progress has been made in the technology of creating gas sensors based on thin films of metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The use of primary alcohols and aldehydes, which are multi-ton products of the petrochemical industry, as starting materials in the catalytic synthesis of nitriles leads to a sharp decrease in the cost of the process. One of the main reasons is the inertness of the starting materials in relation to the reactors where the process goes, but at the beginning, potassium peroxysulfate [ 8 ], manganese dioxide [ 9 ], tetrabutylammonium peroxydisulfate [ 10 ] and others [ 11 ] were used as oxidants in the alcohol ammoxidation reaction. Exceeding the stoichiometric amount of oxidizing agents in the reaction conditions causes the formation of additional products.…”
Section: Introductionmentioning
confidence: 99%